2005
DOI: 10.1128/jb.187.1.231-237.2005
|View full text |Cite
|
Sign up to set email alerts
|

Methionine Sulfoxide Reduction and Assimilation in Escherichia coli : New Role for the Biotin Sulfoxide Reductase BisC

Abstract: Methionine ranks among the amino acids most sensitive to oxidation, which converts it to a racemic mixture of methionine-S-sulfoxide (Met-S-SO) and methionine-R-sulfoxide (Met-R-SO). The methionine sulfoxide reductases MsrA and MsrB reduce free and protein-bound MetSO, MsrA being specific for Met-S-SO and MsrB for Met-R-SO. In the present study, we report that an Escherichia coli metB 1 auxotroph lacking both msrA and msrB is still able to use either of the two MetSO enantiomers. This indicates that additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 32 publications
2
63
0
Order By: Relevance
“…In E. coli, the bisC-encoded biotin sulfoxide reductase is able to reduce both biotin sulfoxide and methionine sulfoxide to biotin and methionine, respectively (41). This dual activity for BisC also was recently demonstrated in Salmonella enterica serovar Typhimurium and linked to the survival of this organism under conditions of oxidative stress.…”
Section: Discussionmentioning
confidence: 95%
“…In E. coli, the bisC-encoded biotin sulfoxide reductase is able to reduce both biotin sulfoxide and methionine sulfoxide to biotin and methionine, respectively (41). This dual activity for BisC also was recently demonstrated in Salmonella enterica serovar Typhimurium and linked to the survival of this organism under conditions of oxidative stress.…”
Section: Discussionmentioning
confidence: 95%
“…Biotine sulfoxide reductase BisC (19) was another candidate that could play a role in selenite reduction, since this molybdoenzyme has been shown to exhibit a wide substrate specificity in vitro, including biotin sulfoxide, DMSO, trimethylamine oxide, and methionine-S-sulfoxide (5,18). In addition, the corresponding gene, bisC, was not present in Rhodobacter sphaeroides 2.4.1, a strain exhibiting a very low level of selenite reduction activity (10-fold lower than R. sphaeroides f. sp.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli produces a non-exported biotin sulfoxide/methionine sulfoxide reductase encoded by the bisC gene (Ezraty et al, 2005;Pierson & Campbell, 1990). BisC is a homologue of the well-characterized E. coli Tat substrate trimethylamine N-oxide (TMAO) reductase (TorA) (Mejean et al, 1994), but is a cytoplasmic enzyme with an N-tail analogous to that identified on NarG (Ezraty et al, 2005;Sargent, 2007b;Turner et al, 2004).…”
Section: Introductionmentioning
confidence: 99%